(untitled) (The International Journal for Scientific Research, 2025)
Cluttered wardrobes impact daily life efficiency and psychological well-being, but there is limited research on gender-specific storage needs. This study investigates the relationship between gender-responsive wardrobe design, storage practices, and the effects of clutter on daily life. A mixed-methods approach was employed, utilizing a survey N=100 and content analysis of IKEA’s 2025 wardrobe catalogue. The survey revealed that 41.9% of respondents were unsatisfied with their current wardrobe organization, and 55.6% struggled to find suitable storage for specific clothing items. Respondents preferred light neutral color palettes (40.6%), minimalist design (42.9%), modular layouts (34.3%), and wooden materials (51%). Content analysis of IKEA’s PAX system highlighted its modular design and adaptability but a lack of gender-specific organizational components. The psychological impact of cluttered wardrobes included a 27% reduction in life satisfaction, 23% decrease in stress, and 31% improvement in workplace concentration following simplification. Gender differences were noted in color preferences, with males choosing cooler tones and warmer hues for female, along with males preferring sturdier materials and females favoring lighter options. This study highlights gender-responsive wardrobes that maintain aesthetic commonalities while incorporating distinct organizational systems. Male-oriented designs should feature fewer, larger compartments, increased hanging space, and simplified organization, whereas female-oriented designs should include numerous smaller compartments, varied hanging heights, and specialized accessory storage. Integrated lighting is recommended to enhance visibility and functionality. The findings highlight the need for adaptable, gender-responsive wardrobe designs that address psychological well-being and organizational effectiveness without explicit gender distinctions.